(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2016)
The aim of this work is determining the reproductive period and display the spatio-temporal variation of Ucides occidentalis in the Gulf of Guayaquil. The reproductive period was determined by the monthly recording of presence/absence of ovigerous females of U. occidentalis in mangroves. Mondragón, Churute and Naranjal were the sampling sites and, all of those are in the province of Guayas located. Inter-annual variation of reproductivity on each site and in all set, were also analyzed. Reproductive stage was recorded on a period of four to five months, starting from December or January and finishing on April or May. Variations among years and sampling sites were observed. Naranjal and Churute displayed one reproductive peak in 2012 (March) and two peaks between 2013-2014 (January and March, respectively), whereas Mondragón presented one peak in 2012 (April) and 2014 (March), respectively, and two peaks on 2013 (January and March, respectively). The current reproductive closed season partially protects Ucides occidentalis, therefore, it is suggested to apply an adaptive management based on a full cooperation of fishermen to optimize the natural stock recovery, and sustainable use of the resource with a low economic and social impact.